MICROBIOLOGICAL CHARACTERISTICS OF SUSHI ACQUIRED IN ESTABLISHMENTS THAT SELL JAPANESE FOOD - SATO, R. A.; ROSSI JUNIOR, O. D.; BÜRGER, K. P.; ÉVORA, P. M. (Ars Veterinaria, 2017)
Food quality control refers to all and any action aimed at improving good practice in hygiene procedures and food handling. Therefore, there is a continuous need to obtain data, study and monitor the production and marketing in food industry thus producing a safe food, free from any contamination that may cause damage to the consumer´s health. So this study evaluated the microbiological quality of sushi bought in two types of establishments: 15 restaurants specialized in Japanese food and 15 non-specialized restaurants from the Ribeirão Preto - SP region . The populations of heterotrophic mesophiles and psychrotrophic microorganisms ranged from 3,9 x 102 to 1,7 x 107CFU.g-1 and 7,5 x 102 to 1,4 x 109CFU.g-1, respectively. All samples presented Staphylococcus spp. with populations ranging from 2,0 x 102 to 3,8 x 105CFU.g-1, where 23,3% were classified as positive coagulase Staphylococcus and 13.3% had population values above the established limit. Thermotolerant coliforms were found in 60,0% of the samples and 33,3% of them were above the established thermotolerant coliform limit. The presence of Staphylococcus aureus and Escherichia coli were identified in 16,7% and 30,0% of the samples, respectively. Salmonella sp. and Vibrio parahaemolyticus were not isolated in this research. There was no difference in the microbiological quality of sushi offered between the two types of establishments. According to the results it is concluded that sushi is a potential foodborne disease food and the non-standard samples reflect the need to properly train the food handlers.